Elimination of micro-organisms by drinking water treatment processes : a review - Hijnen, W. A. M. 1956- (KWR Watercycle Research Institute series., 2010)
The overall aim of this book is to present default values for the micro-organisms elimination or inactivation credit of universally used processes in water treatment (MEC or MIC). The growing interest in Quantitative Microbial Risk assessment (QMRA) for safe drinking water requires such data. These MEC or MIC values have been calculated from research on elimination of viruses, bacteria and bacterial spores and protozoa (oo)cysts (Cryptosporidium and Giardia) by these treatment processes published in the international literature. The data have been selected on the base of different quality criteria related to information on applied experimental conditions and used methods. Furthermore the studies have been categorized on base of their similarities with 'real world' conditions (selected micro-organisms, scale and conditions of the tested processes).